Detection of Nicotine in Urine of Passive Smokers Exposed to Cigarette Smoke From Smoking and Non-Smoking Families - Aolani, Almira Zaida; Fihiruddin, Fihiruddin; Urip, Urip; Tatontos, Erlin Yustin (Jurnal Analis Medika Biosains (JAMBS), 2025)
Passive smokers are vulnerable to nicotine exposure, which can increase the risk of health problems. Nicotine is a chemical compound in tobacco that causes dependence and can be detected in urine as metabolites like cotinine. This study aimed to detect nicotine in the urine of passive smokers exposed to cigarette smoke from smoking and non-smoking families in Genggelang Village. An analytical observational method with a cross-sectional design was used. The sample consisted of 24 respondents selected by purposive sampling, divided into two groups. Urine samples were tested using a nicotine test strip and analyzed descriptively. The results showed that among 12 passive smokers from smoking families, one respondent tested positive for nicotine. Meanwhile, all 12 respondents from non-smoking families tested negative. These findings indicate that passive smokers living with smoking families are still at risk of nicotine exposure through second hand smoke in the household environment.